Association between intraoperative steroid and postoperative mortality in patients undergoing craniotomy for brain tumor - He, Jialing; He, Shuanghong; Zhang, Yu; Tian, Yixin; Hao, Pengfei; Li, Tiangui; Xiao, Yangchun; Peng, Liyuan; Feng, Yuning; Cheng, Xin; Deng, Haidong; Wang, Peng; et al. (Frontiers in Neurology, 2023)
Background Despite the widespread use of intraoperative steroids in various neurological surgeries to reduce cerebral edema and other adverse symptoms, there is sparse evidence in the literature for the optimal and safe usage of intraoperative steroid administration in patients undergoing craniotomy for brain tumors. We aimed to investigate the effects of intraoperative steroid administration on postoperative 30-day mortality in patients undergoing craniotomy for brain tumors. Methods Adult patients who underwent craniotomy for brain tumors between January 2011 to January 2020 were included at West China Hospital, Sichuan University in this retrospective cohort study. Stratified analysis based on the type of brain tumor was conducted to explore the potential interaction. Results This study included 8,663 patients undergoing craniotomy for brain tumors. In patients with benign brain tumors, intraoperative administration of steroids was associated with a higher risk of postoperative 30-day mortality (adjusted OR 1.98, 95% CI 1.09–3.57). However, in patients with malignant brain tumors, no significant association was found between intraoperative steroid administration and postoperative 30-day mortality (adjusted OR 0.86, 95% CI 0.55–1.35). Additionally, administration of intraoperative steroids was not associated with acute kidney injury (adjusted OR 1.11, 95% CI 0.71–1.73), pneumonia (adjusted OR 0.89, 95% CI 0.74–1.07), surgical site infection (adjusted OR 0.78, 95% CI 0.50–1.22) within 30 days, and stress hyperglycemia (adjusted OR 1.05, 95% CI 0.81–1.38) within 24 h after craniotomy for brain tumor. Conclusion In patients undergoing craniotomy for benign brain tumors, intraoperative steroids were associated with 30-day mortality, but this association was not significant in patients with malignant brain tumors.